Solution:
we have been asked to find
The expression is equivalent to ![7/10-2/10](https://tex.z-dn.net/?f=%207%2F10-2%2F10%20)
we can simplify the given expression as below
![\frac{7}{10}-\frac{2}{10}=\frac{7-2}{10}\\ \\ \Rightarrow \frac{7}{10}-\frac{2}{10}=\frac{5}{10}\\ \\ \text{Simplify we get}\\ \\ \frac{7}{10}-\frac{2}{10}=\frac{1}{2}\\](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B10%7D-%5Cfrac%7B2%7D%7B10%7D%3D%5Cfrac%7B7-2%7D%7B10%7D%5C%5C%20%5C%5C%20%5CRightarrow%20%5Cfrac%7B7%7D%7B10%7D-%5Cfrac%7B2%7D%7B10%7D%3D%5Cfrac%7B5%7D%7B10%7D%5C%5C%20%5C%5C%20%5Ctext%7BSimplify%20we%20get%7D%5C%5C%20%5C%5C%20%5Cfrac%7B7%7D%7B10%7D-%5Cfrac%7B2%7D%7B10%7D%3D%5Cfrac%7B1%7D%7B2%7D%5C%5C%20)
Hence the simplified expression , equaivalent to the given expression is 1/2.
1790988582563.6448is your answer. All you do is multiply 14 times 1.2, which equals 16.8. Then you do 16.8 times itself. 16.8 x 16.8 = 282.24. Then 282.24 times itself, and so on so forth.
4:1 is the answer............
Y = 5 - 4x
5 - 4x = x^2 - 2x - 19
0 = x^2 + 2x -24
0 = (x + 6)(x - 4)
Therefore x = -6 (Given) or 4
x = 4, y = -9
(4,-9) is the other solution